Knowledge, Attitude and Practice Regarding Covid-19 Pandemic among Dental Practitioners of India: A Questionnaire-based Survey - Gunjan Srivastava; Swagatika Panda; Subrat K Padhiary; Neeta Mohanty (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background- Owing to high viral load in saliva, dental practitioners are not only susceptible forexposure during Covid-19 outbreak but also post pandemic era. During the period of evolving facts andrecommendations of WHO for maintaining precautions this study is an effort to understand the preparednessof dental practitioners to resume their practice.Objectives- The objective of this study is to evaluate the knowledge, attitude and practice of dentalpractitioners regarding the Covid-19 pandemic.Methods- This cross-sectional study was conducted among dental practitioners of India through an onlinequestionnaire-based survey to collect data. The questionnaire was divided into sections containing structuredmultiple-choice questions about the knowledge, attitude and practice of dental practitioners.Result- Upon analyzing 311 responses it has been observed that majority of dental practitioners wereaware of common symptoms of Covid-19 and about the modes of transmission of the disease. They possessadequate knowledge about use of Personal Protective Equipment (PPE) with 88.4 % suggesting to useit while performing aerosol generating procedure. Their awareness about a Covid-19 patient becomingnoninfectious is inadequate with only 10% reporting 30 days. Attitude and practice of dental practitionersregarding Covid-19 were stratified on the basis of years of practice.Conclusions -Dental practitioners possess adequate knowledge about standard precaution protocol althoughthey are less aware about transmission-based precaution specific to Covid-19 situation. This study attempts tohighlight some facts about Covid-19 which will enlighten the dental practitioners before resuming practice.